Penerapan Metode Eksperimen Telur dan Air Garam sebagai Media Pembelajaran Sains Dasar IPAS Kelas IV di Mi Jam’iyatul Mubtadiin - Intan Nurlaila; Muhammad Suwignyo Prayogo; Ika Dini Akmalia; Sindi Wulandari (Lembaga Pengembangan Kinerja Dosen, 2025)
This study discusses the application of a simple experimental method using eggs and salt water as a medium for teaching basic science at MI Jam'iyatul Mubtadiin. The main objective is to improve students' understanding of the concepts of mass and buoyancy through direct experience. The research method used was a descriptive qualitative approach with fourth-grade students as subjects. The learning process was carried out through simple experimental steps: preparing fresh water, adding salt, and observing changes in the position of the eggs in the solution. Data were collected through observation, interviews, and . The results showed that this experimental method was able to attract students' interest, increase active participation, and make abstract concepts easier to understand. In addition, this simple experiment-based learning also trains students' critical thinking skills and curiosity. Thus, the use of egg and salt water experiments can be an alternative to effective, inexpensive science learning media that is suitable for the characteristics of elementary school students.